Racial Discrimination in Child Protection - Baron, E. Jason,Doyle, Joseph J.,Emanuel, Natalia,Hull, Peter,Ryan, Joseph P. (National Bureau of Economic Research, 2023)
Ten percent of Black children in the U.S. spend time in foster care–twice the rate of white children. We estimate unwarranted disparities in foster care placement decisions, adjusting for differences in the potential for future maltreatment by leveraging the quasi-random assignment of cases to investigators. Using a sample of nearly 220,000 maltreatment investigations, we find that Black children are 1.7 percentage points (50%) more likely to be placed into foster care following an investigation than white children conditional on subsequent maltreatment potential. This disparity is entirely driven by white investigators and by cases where maltreatment potential is present, in which Black children are twice as likely to be placed as white children (12% vs. 6%). These results suggest white children may be harmed by
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Kinderschutz; Kinder; Ethnische Diskriminierung; Pflegeeltern; USA; Instrumental Variables (IV) Estimation; General Welfare; Well-Being; Fertility; Family Planning; Child Care; Children; Youth; Economics of Minorities; Races; Indigenous Peoples; and Immigrants; Non-labor Discrimination